The Influence of Eco-Control, Environmental Performance and Media Exposure on CSR Disclosure - Putri, Syifa Diana; Yuliandhari, Willy Sri (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
The company has a responsibility to disclose corporate social responsibility. This study analyzes companies listed on the Indonesia Stock Exchange in the consumer non-cyclical sector for 2018-2022, focusing on eco-control (performance measurement, budgeting, and incentives), environmental performance, and media exposure, as well as their impact on corporate social responsibility disclosure. A quantitative approach, including panel data regression and descriptive statistics, was used to test the hypotheses. The sampling technique employed was purposive sampling, resulting in a sample of 10 companies with 50 observations. The results of the study indicate that performance measurement, budgeting, and media exposure have an impact on corporate social responsibility disclosure. However, no impact was found for incentives and environmental performance on corporate social responsibility disclosure.